The effects of particle angularity on low-stress three-body abrasion-corrosion of 316L stainless steel - Stachowiak, Grazyna; Salasi, Mobin; Rickard, William; Stachowiak, Gwidon (Elsevier, 2016)
© 2016 Elsevier Ltd This study investigates the effects of particle angularity on the tribo-electrochemical behaviour of 316L stainless steel under low-stress three-body abrasion–corrosion conditions. Different angularity particles were delivered to the interface between the samples and a rotating rubber counterface, while changes in current with time were potentiostatically monitored. Based on a linear relationship existed between tribological factors (load and speed) and the average current evolved, an empirical correlation is proposed and possible underlying mechanisms are discussed. The effects of particle angularity on the surface and sub-surface damage are also demonstrated. It was found that increasing particle angularity improved their depassivation efficiency.